Nitrogen Fertilization Shapes Soil Microbial Diversity and Ecosystem Multifunctionality by Modulating Soil Nutrients - Yaoquan Zhang; Zhuzhu Luo; Liangliang Li; Lili Nian; Lingling Li; Yining Niu; Renyuan He; Jiahe Liu (Microorganisms)
Soil microbial communities play an important role in driving diverse ecosystem functions and ecological processes and are the main driving force for maintaining biogeochemical cycles. To investigate the effects of nitrogen fertilizer addition on soil microbial community characteristics and ecosystem multifunctionality in alfalfa fields, a field experiment was conducted in the semi-arid region of the Loess Plateau. Ecological network analysis revealed a strong cooperative relationship among bacterial community species under the N100 treatment, while a strong competitive relationship was observed among fungal community species under the N50 treatment. Furthermore, compared with the control check, the soil carbon nutrient function, ecosystem multifunctionality and grassland productivity of N150 treatment increased by 45.17%, 34.01%, and 7.92%, while the soil phosphorus function decreased by 13.44%. Additionally, soil pH significantly influences ecosystem multifunctionality, soil carbon nutrient function, and grassland productivity. Soil water content notably affects the soil phosphorus nutrient function, while soil microbial diversity has a significant impact on grassland productivity and soil potassium nutrient function. The above results suggest that alterations in soil nutrient levels influence ecosystem multifunctionality by regulating microbial community diversity, offering new insights into the mechanisms by which nutrients impact soil microbial communities and ecosystem properties.